Clinical outcomes after implantation of a trifocal toric intraocular lens - Kretz, Florian Tobias Alwin; Breyer, Detlev Richard Hans; Klabe, Karsten; Hagen, Phillipp; Kaymak, Hakan; Koss, Michael Janusz; Gerl, Matthias; Müller, Matthias; Gerl, Ralf-Hellmar; Auffarth, Gerd U. (Journal of refractive surgery, 2015)
To evaluate the visual, refractive, and contrast sensitivity outcomes, as well as the level of photic phenomena, after cataract surgery with implantation of a trifocal diffractive toric intraocular lens (IOL).
Gesehen am 28.07.2020